Investigation of a Vacuum Ejector Used in a Dynamic Function Vehicle Tire Air Control Valve - Y. S. Korkmaz; A. Kibar; K. Suleyman Yigit; E. Erturk; Z. Doğruyol (Journal of Applied Fluid Mechanics)
A critical component of a central tyre inflation system (CTIS) is the tyre valve. When positive pressure air is directed to the valve, it allows air to enter the tyre, increasing the tyre’s internal pressure. Conversely, when vacuum pressure is applied, the tyre pressure decreases. Consequently, the tyre valve must be capable of generating negative pressure when necessary to function effectively. While the CTIS includes a compressed air reservoir and a pressure pump for reservoir filling, it lacks a dedicated vacuum pump to create negative pressure. Instead, negative pressure is generated by an ejector that utilises the Venturi effect to accelerate the air through an orifice, creating low pressure using pressurised air from the reservoir. The primary advantage of this design is its ability to generate negative pressure without an additional component, such as a vacuum pump, relying solely on the existing high-pressure air. This study presents both experimental and numerical investigations of a vacuum ejector designed to generate negative pressure. The experimental results align closely with the numerical simulations. Furthermore, the study explores the impact of varying the throat diameter of the vacuum ejector to enhance fluid velocity, with the optimal performance observed at −98 kPa for a 1 mm throat diameter. For throat diameters of <1 mm, the flow becomes unstable, and at 0.2 mm, the flow is completely obstructed, rendering the system inoperative.